2020
DOI: 10.1177/0266242620960711
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating the female successor–leader role within family business succession in China

Abstract: This article explores the approaches of identity construction used by Chinese daughters while negotiating the successor–leader role within family businesses. A qualitative interpretivist approach was adopted to understand daughter views on gender, family business leadership and succession, as well as the approaches adopted to negotiate the role of female successor/leader in the Chinese family business. Twenty semi-structured interviews were conducted with both actual and potential female successors. Three appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 86 publications
(167 reference statements)
2
38
0
Order By: Relevance
“…It seems that female heirs may be focusing on normative issues, regardless of what the founder may have done. This is in line with the results reported by Xian et al (2021) [85] on identity construction in the Chinese family context, who revealed that female successor leaders adjusted their leadership identity to the degree of conformity to conventional gender expectations. As a result of this conceptualisation, successor women presented three approaches to leadership identity: temporary leader, second leader and independent leader.…”
Section: Gender Intergenerational Succession and Csrsupporting
confidence: 91%
“…It seems that female heirs may be focusing on normative issues, regardless of what the founder may have done. This is in line with the results reported by Xian et al (2021) [85] on identity construction in the Chinese family context, who revealed that female successor leaders adjusted their leadership identity to the degree of conformity to conventional gender expectations. As a result of this conceptualisation, successor women presented three approaches to leadership identity: temporary leader, second leader and independent leader.…”
Section: Gender Intergenerational Succession and Csrsupporting
confidence: 91%
“…The most important components of the strategy of a planned transfer of entrepreneurs are the detailed consideration of the exit situation in relation to the form of the company and the desired transitional form, as well as the consideration and coordination of the precise objectives of the transfer of the entrepreneur between all parties involved as can be also seen in the works of Xian (2021) [28].…”
Section: Discussionmentioning
confidence: 99%
“…These are mainly recent works with a release date of more than 2000. The latest work is the journal article from Xian 2021 [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Girls act as second leaders and remain involved in decision making. Chinese girls must face the fact that women are second only to men by the realities of existing Chinese culture and become independent leaders [13].…”
Section: Introductionmentioning
confidence: 99%